Inhibitors of bacterial and plants urease. A review - Macegoniuk, Katarzyna (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2013)
Urease is an important virulence factor for Helicobacter pylori and Proteus mirabilis as well as in environmental transformations of certain nitrogenous compounds. Urea hydrolysis caused by these microorganisms leads to increased pH and ammonia toxicity and enables bacterial colonization of the human gastric mucosa and urinary tract formation of struvite and carbonate-apatite stones. Due to the possibility of medical applications the development of novel, selective and efficient classes of urease inhibitors which satisfy the low toxicity requirement for human health and have low environmental impact is necessary. In this article are described the various urease inhibitors used so far by researchers, especially in the last few years.